THE INFLUENCE OF MASTERING TARGET-LANGUAGE CULTURE ON THE STUDENTS’ LANGUAGE SKILLS - Nurun Hidayati; Endang Fauziati; Sri Samiati Tarjana (Journal of English Education, 2017)
Mastering language in English as a Foreign Language (EFL) context requires many aspects related to the language itself. This paper aimed to explore one of the aspects which influenced the students’ language skills which were the target-language culture. The current paper utilized qualitative research in the form of case study. Besides, the participants were the fourth-semester students of English department in Universitas Mataram. The method of collecting the data employed interview and observation. To validate the data, the triangulations of the data source and data collection method were utilized. At the end, to analyze the data, the interactive model was employed. The result revealed that 1). The students get the influences on their reading and speaking skills by learning target-language culture in Cross Culture Understanding (CCU) class, 2). The influence in reading can be seen when the students’ gaining new vocabulary from the texts they read and produced it when they spoke, and 3). In speaking, the students’ accent still affected greatly by the interference of their native accent and culture. The paper also suggests that employing the mixed method (quantitative and qualitative methods) might be useful and more preferable to see the influence on the students’ language skills as the effect of attending the CCU class and learning the target-language culture.